2016
DOI: 10.1002/ijgo.12046
|View full text |Cite
|
Sign up to set email alerts
|

The impact of laparoscopic cystectomy on ovarian reserve in patients with unilateral and bilateral endometrioma

Abstract: Laparoscopic cystectomy was associated with post-operative decreases in serum AMH, particularly with bilateral involvement and endometriomas at least 50 mm in diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…These results are in agreement with Kashi et al [23] who concluded from his study that Laparoscopic cystectomy was associated with post-operative decreases in serum AMH, particularly with bilateral involvement (p value in bilateral = 0.029 and in unilateral = 0.046) and endometriomas at least 50 mm in diameter ( p value in ≥ 50mm was < 0.001 and in <50mm was 0.015).…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with Kashi et al [23] who concluded from his study that Laparoscopic cystectomy was associated with post-operative decreases in serum AMH, particularly with bilateral involvement (p value in bilateral = 0.029 and in unilateral = 0.046) and endometriomas at least 50 mm in diameter ( p value in ≥ 50mm was < 0.001 and in <50mm was 0.015).…”
Section: Discussionsupporting
confidence: 92%
“…Other factors could also affect the ovarian reserve, such as cyst size, laterality of the endometriomas, and surgical skill of the physician performing cyst stripping . However, scientific data regarding these factors are contradictory and the mentioned variables might not have any tangible influence .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from AFC and basal hormone, anti-Müllerian hormone (AMH) level is also demonstrated to predict the magnitude of ovarian reserve as well as controlled ovarian stimulation (COS) responses [18,22]. Endometrioma cystectomy, especially bilateral surgery, is deleterious with respect to ovarian reserve for AMH, which decreased significantly based on a recent systematic review and meta-analysis and previous studies [12,18,23,24].…”
Section: Introductionmentioning
confidence: 99%